Reassessing Moral Education: A Critical Evaluation of Gendang Bugis as Pedagogical Practice in the Digital Era - Rachmat Rachmat; Sunarto Sunarto; Agus Cahyono (Journal Evaluation in Education (JEE), 2025)
Purpose of the study: In the context of the digital era, the transmission of moral values faces increasing challenges due to the dominance of globalized, visual, and fast-paced content. This study aims to explore how Gendang Bugis a traditional Bugis musical performance, functions as a medium of moral pedagogy when represented and recontextualized on digital platforms Methodology: This research adopts an exploratory qualitative approach, employing digital ethnographic techniques. Data were collected through in-depth interviews, participatory observations, and content analysis of Gendang Bugis representations on social media platforms including YouTube, Instagram, and TikTok. Survey instruments: semi-structured interview guide and observation checklist. Main Findings: The main results indicate that digital performances of Gendang Bugis effectively transmit core moral values such as discipline, respect, solidarity, and cooperation. Senior performers act as moral role models, while youth audiences engage through affective and interactive virtual platforms. This online interaction fosters deeper value internalization. Moreover, digital platforms broaden access, promote intergenerational moral dialogue, and reinforce the pedagogical strength of traditional arts, even amid concerns over cultural authenticity and shifting modes of transmission in modern contexts Novelty/Originality of this study: This study presents a novel evaluative framework that integrates traditional performance pedagogy with digital ethnography. The results highlight the active role of digitalized traditional arts in moral education. It emphasizes the urgency of developing culturally grounded, digitally adaptive educational content and encourages the integration of traditional arts into both formal and informal education systems in a relevant and contextual manner.